Exploring critical factors of green business failure based on Grey-Decision Making Trial and Evaluation Laboratory (DEMATEL) - Cui, Li; Chan, Hing Kai; Zhou, Yizhuo; Dai, Jing; Lim, Jia Jia (Journal of business research, 2019)
Business failure is an important issue for companies in the 21st century, and green business is of global concern. Therefore, it is of vital importance to reveal the critical factors that could lead to green business failure. Nevertheless, existing research has not fully addressed this yet. This study adopts the company life cycle theory to identify such critical factors. The Decision Making Trial and Evaluation Laboratory (DEMATEL) method is applied to convert the expert opinion into quantifiable data, and grey relational analysis is used to take the imprecise information into account in order to improve the validity of the results. Research frameworks constructed from company life cycle is able to reflect the critical factors that lead to green business failure at different development phases. Meanwhile, the adoption of Grey DEMATEL improves the accuracy of assessment, and the result of assessment provides feasible and practical suggestions for decision-making.